How Microlearning Can Benefit Education: A Study of Factors and Trends in the Use of Microlearning - Ranggana, Alfaza; Rasim, Rasim; Megasari, Rani (Universitas Pahlawan Tuanku Tambusai, 2025)
Microlearning has become one of the approaches that has become increasingly in demand in the last two decades along with the increasing need for flexible and digital technology-based learning. This research aims to define the concept of microlearning and identify research trends and factors that drive its implementation. The method used is a bibliometric analysis of microlearning-themed publications obtained from the ScienceDirect database from the initial appearance of the term until 2024. The analysis was carried out based on three main aspects, namely the frequency of publications, the number of citations, and the network of co-emergence and co-authorship. The results of the study show a significant increase in the number of microlearning-related publications over the past two decades. The publications with the highest citations were mostly from the pre-COVID-19 pandemic period, while 99% of documents did not show a strong pattern of authorship collaboration. In addition, microlearning is defined through three main factors, namely mobile device use, social connectedness, and time constraints. These findings confirm that research on microlearning remains relevant and has the potential to be an important foundation for the development of digital learning strategies in the future